Characteristics Of Toraja Culture-Based Mathematics Learning Model - Suri Toding Lembang; Nurdin Arysad; Bernard, Bernard; I Ketut Linggih (Cita konsultindo, 2024)
This research examines a Toraja culture-based mathematics learning model, known as Beradat, through a literature study method. The Beradat model consists of five continuous stages: ma'parapa (motivation and problem identification), ma'kombongan (problem posing and small group discussion), ma'kombongan kalua' (class discussion), feedback, and mantaa and didosa (reward and reinforcement). Each stage is designed to create a conducive learning atmosphere, respect local culture, and develop students' mathematical skills and understanding comprehensively. The research found that the Beradat model has a number of advantages, including high cultural integration, increased active student engagement, a motivating reward system, and the development of social skills and a positive classroom environment. The model also adopts the principles of problem-based learning, encourages group work, and creates a respectful social system. However, there are challenges in its implementation, such as the need for strong training and support for teachers, time challenges in a collaborative approach, and potential implementation failure if not well supported. Overall, the Toraja culture-based mathematics learning model has great potential in improving students' mathematical understanding and social skills. However, its success requires adequate preparation and support to be effectively implemented in various eduational contexts.